2019
DOI: 10.1096/fj.201900306rr
|View full text |Cite
|
Sign up to set email alerts
|

Ankle loading ameliorates bone loss from breast cancer–associated bone metastasis

Abstract: Breast cancer is a serious health problem that preferentially metastasizes to bone. We have previously shown that bone loss can be prevented by mechanical loading, but the efficacy of ankle loading for metastasis‐linked bone loss has not been investigated. This study showed that body weight was decreased after inoculation of tumor cells, but ankle loading restored a rapid weight loss. The nonloading group exhibited a decrease in bone volume/tissue volume (BV/TV), trabecular thickness, and trabecular number (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Since bone is a mechano‐sensitive organ, moderate pulsating loading, oscillatory compressive loads, can be applied to various synovial joints in a form of elbow loading, knee loading and ankle loading . Joint loading can change intramedullary pressure of bone cavities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since bone is a mechano‐sensitive organ, moderate pulsating loading, oscillatory compressive loads, can be applied to various synovial joints in a form of elbow loading, knee loading and ankle loading . Joint loading can change intramedullary pressure of bone cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Since bone is a mechano-sensitive organ, moderate pulsating loading, oscillatory compressive loads, can be applied to various synovial joints in a form of elbow loading, knee loading and ankle loading. [17][18][19][20] Joint loading can change intramedullary pressure of bone cavities. The moderately changing pressure may generate fluid flow in a lacuna canalicular network in bone cortex, and activate anabolic genes in bone.…”
mentioning
confidence: 99%
“…Using H&E stained femoral sections, we determined A.ar/T.ar (in %, T.ar = total tissue area, and A.ar = adipocytes area), adipocyte perimeter, adipocyte number [30] and B.ar/T.ar (in %, T.ar = total tissue area, and B.ar = trabecular bone area), as well as bone trabecular circumference in the 1.9 mm 2 sample area of the proximal femoral growth plate [31]. Furthermore, MacNeal's stained sections were used to determine the osteoblast number on the trabecular bone surface (osteoblasts number/bone surface, N.Ob/BS/mm) [32].…”
Section: Histology Macneal's and Immunohistochemistry Assaysmentioning
confidence: 99%
“…13 We have developed joint loading modalities, 14 in which dynamic lateral loads are applied to synovial joints such as the elbow, 15 knee, 16 and ankle. 17,18 It is considered that mechanical loading induces dynamic deformation in the epiphysis that drives the alteration in intramedullary pressure in the medullary cavity and interstitial fluid flow in the lacunocanalicular network. 14 We previously reported that knee loading stimulated wound healing in the femoral neck and tibia, 19,20 prevented cartilage degeneration, 21,22 and promoted vessel remodeling and bone healing in osteoporosis of the femoral head.…”
Section: Introductionmentioning
confidence: 99%